Late Renaissance Garden Art in the Carpathian Basin - Fekete, Albert (Acta Geographica Debrecina Landscape & Environment series, 2020)
The aim of the article was to find, scientifically define and locate the most frequent occurrences of the Late Renaissance garden units of the Carpathian Basin. This article - as partial result of a research work entitled "Castle Garden Inventory in the Carpathian Basin" and conducted by teachers and students of the Faculty of Landscape Architecture and Urbanism of Szent István University, Budapest - aims to identify through historical research, on-site visits and assessments the current status of 148 Late Renaissance residency gardens located in seven different countries of the Carpathian Basin (Austria, Hungary, Slovakia, Ukraine, Romania, Croatia and Slovenia). Based on the archival and literary sources as well as the field studies carried out, we defined the spatial distribution of Late Renaissance residential gardens, we delineated six very characteristic Late Renaissance garden units and we defined the most typical Late Renaissance garden features for the region. At the same time, we explored and documented still existing values of garden history at some locations from the Renaissance era.